Peripheral gene dysregulation in Negr1-deficient mice: insights into possible links with affective behavior - Maigoro, Abdulkadir Yusif; Kim, Jangrae; Cho, Seoyeon; Yoo, Ara; Lee, Soojin (Frontiers in Molecular Neuroscience, 2025)
IntroductionNeuronal growth regulator 1 (NEGR1) is a brain-enriched membrane protein with mild expression in peripheral tissues such as adipose tissue and skeletal muscle. Genome-wide association studies have implicated NEGR1 as a risk factor for human diseases including obesity, autism, and depression, but its molecular function remains poorly understood.MethodsTo explore NEGR1’s role in peripheral-to-brain communication, we conducted RNA-seq analysis on four peripheral tissues—intestine, skeletal muscle, liver, and epididymal white adipose tissue—collected from Negr1 knockout mice. Differentially expressed genes (DEGs) were identified and subjected to Gene Ontology (GO) enrichment analyses.ResultsThe DEG analysis revealed dysregulation of ion channels and transporters, potentially contributing to AP-1-mediated inflammatory responses in peripheral tissues. Additionally, interleukin (IL)-17 signaling emerged as a key pathway that may mediate systemic inflammation in Negr1-deficient mice.DiscussionThese findings suggest a novel role for NEGR1 in modulating peripheral inflammatory responses and support the hypothesis that peripheral immune dysregulation may contribute to depressive-like behaviors in Negr1-deficient mice. This work enhances our understanding of NEGR1’s function in peripheral tissues and its possible involvement in peripheral-central immune crosstalk relevant to psychiatric disorders.